The Influence of Tax Management Transparency and Tax Fairness on Taxpayer Trust in the KPP of East Tangerang City in 2020 - Maulani, Agus (Indonesian Scientific Publication, 2023)
This research was conducted at KPP Pratama Kota Tangerang Timur. Research aims to find out the effect of transparency of tax management and taxpayer trust on taxpayer trust. This research uses a quantitative approach with survey research. This research sample was the taxpayers at KPP Pratama Kota Tangerang Timur and obtained 100 respondents. Data analysis uses multiple linear regressions. In this study, the authors used SPSS 25. The results of this study showed that The Transparency of Tax Management (X1) did not have a significant effect on taxpayer trust (Y) in the East Tangerang City Primary KPP only by 21.9% and the remaining 78.1% was influenced by other factors outside in this research model that were not studied by researchers. Tax Justice (X2) does not have a significant effect on taxpayer trust (Y) in KPP Pratama Kota Tangerang Timur only by 28.4% and the remaining 71.6% is influenced by other factors outside in this research model that are not studied by researchers. Other results, that together transparency of tax management (X1) and tax justice (X2) did not have a significant effect on taxpayer trust (Y) in KPP Pratama Kota Tangerang Timur only by 32.7% and the remaining 67.3% was influenced by other factors outside in this study model that were not studied by researchers.